PENGARUH MOTIVASI (KEBUTUHAN FISIOLOGIS, KEBUTUHAN RASA AMAN, KEBUTUHAN SOSIAL, KEBUTUHAN PENGHARGAAN, KEBUTUHAN AKTUALISASIDIRI) TERHADAP KINERJA PERAWAT ( Studi Kasus Di Instalasi Bedah Rumah Sakit Khatolik St. Vincentius A Paulo Surabaya ) - Debora Yublina Rumokoy; Rini Fatmawati (Faculty of Social and Political Science, 2013)
This study aims to determine the effect of motivation on the performance of simultaneous installation of Surgical nurse at Catholic Hospital St. Vincentius A Paulo Surabaya. Population in this study is the installation of Surgical nurse Catholic Hospital St. Vincentius A Paulo Surabaya to 70 nurses, and technical pens gamhilan purposive sample sample (sample intended). While the technique of multiple linear regression analysis using the F test and t test, and the coefficient determenasi accompanied by classical assumption that is multikolinieritas and heterokedastisitas. Used to test the validity of Pearson product moment correlation technique, while primarily known for reliability alpha coefficient Cronbanch.From the results of research known independent variable physiological needs (XI), needs a sense of security (X2), social needs (X3), the needs appreciation (X4), and the need for self-actualization (X5) together - while providing a significant influence on employee performance (Y) as a bound variable. This can be found by comparing the Phming (59,688) with the level of offense (0,000), which is under the allowed error rate (0,05). Based on the calculation of the t test was performed to note that the independent variables partially significant effect on the dependent variable. It is known from the tfumng independent variable has a value greater than Z^/. Each regression coefficient independent variable is 0, 173 XI • 0.192 X2 i 0.193 X3 i 0.164 X4 V 0.186 X5 with the constant of 0.352 so that the resulting regression equation as follows :Y= 0,352+ 0,173 XI+ 0,192X2 +0,193 X* +0,164 X4+0,186 X5 Variable needs a sense of security (X2) is the dominant influential variables on the performance of employees with a beta value of 0.281 size. Meanwhile, the value of R2 as large as 0.786, which means that the influential independent variables together - be as big as 78.6% on the dependent variable while the remaining 21.4% is influenced by other variables beyond the variables of the study.